ANALISIS PERAWATAN MESIN DRYER MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE DAN OVERALL EQUIPMENT EFFECTIVENESS UNTUK PENINGKATAN KUALITAS CRUMB RUBBER DI PT XYZ - Sarah Rumapea; Olivia Rachmanita Saidi; Anita Christine Sembiring (Universitas Putera Batam, 2026)
PT XYZ is a company engaged in the processing of rubber into crumb rubber products, supported by various machines and equipment to achieve optimal productivity. One of the main machines in the production process is the dryer, which functions to reduce the moisture content in the product. The main issue identified is that the effectiveness of the dryer machine, as measured using the Overall Equipment Effectiveness (OEE) method, shows values of 84%, 84%, and 82% during August–October 2025, which are below the world-class standard of 85%. Analysis using the Reliability Centered Maintenance (RCM) and Failure Mode and Effect Analysis (FMEA) methods indicates that critical components such as chain, box rail, and box wheel have a high risk of failure based on their Risk Priority Number (RPN) values, thus requiring special attention in determining maintenance actions. The application of the Reliability Centered Maintenance (RCM) method identifies the most appropriate maintenance actions for critical components through the task selection process based on the characteristics of each failure mode. These results indicate that prioritizing maintenance on critical components can reduce potential failures and improve machine effectiveness in the production process.